Odd factoring in textbook

Though this is for a calculus problem, I've gotten all the calc worked out. I just don't understand how the book came to this conclusion after factoring!

$\displaystyle 3x^2 - 12x + 11 = 0$

The answer the book comes to is

$\displaystyle (6 + sqrt(3)) / 3 $

$\displaystyle (6 - sqrt(3)) / 3 $

The way I did it in the first place was:

$\displaystyle 3x^2 - 12x = -11$

$\displaystyle 3x(x - 4) = -11$

Therefore

$\displaystyle x = -11 / 3$

$\displaystyle x = -7$

What were they doing in my textbook? Unfortunately they give no clues and I've been staring at it for 15 minutes now.